2022
DOI: 10.1108/ijsms-03-2022-0055
|View full text |Cite
|
Sign up to set email alerts
|

Service encounter and repurchase intention in fitness centers: perceived value as a mediator and service innovativeness as a moderator

Abstract: PurposeThis study examined the relationships between service encounter, perceived value, and repurchase intention in the fitness service sector through the theoretical lens of service-dominant logic. In addition, the mediating role of perceived value and the moderating role of service innovativeness were examined.Design/methodology/approachParticipants (n = 806) were drawn from fitness center customers in Taiwan using a convenience sampling technique. Partial least square structural equation modeling was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 114 publications
(394 reference statements)
2
57
0
Order By: Relevance
“…Enterprises need proper pricing tactics to generate the greatest investment returns and to control their operations' efficiency. Consistent with the findings of past studies, Curves' pricing strategies have enabled stable profit increases (Wang and Chiu, 2022). Respondents stated that the profit formula in Curves' operating model consists of word-of-mouth marketing (i.e., word-of-mouth advertising among customers), which accounts for up to 50% of monthly profit; brand marketing (i.e., using signboards, the internet, and advertisements to increase brand impressions), which accounts for up to 25% of monthly profit; and proactive client development, including distributing flyers and newsletters and direct mail, which accounts for up to 25% of monthly profit.…”
Section: 'Emphasis On High Transparency Of Prices (A)supporting
confidence: 87%
See 4 more Smart Citations
“…Enterprises need proper pricing tactics to generate the greatest investment returns and to control their operations' efficiency. Consistent with the findings of past studies, Curves' pricing strategies have enabled stable profit increases (Wang and Chiu, 2022). Respondents stated that the profit formula in Curves' operating model consists of word-of-mouth marketing (i.e., word-of-mouth advertising among customers), which accounts for up to 50% of monthly profit; brand marketing (i.e., using signboards, the internet, and advertisements to increase brand impressions), which accounts for up to 25% of monthly profit; and proactive client development, including distributing flyers and newsletters and direct mail, which accounts for up to 25% of monthly profit.…”
Section: 'Emphasis On High Transparency Of Prices (A)supporting
confidence: 87%
“…Studies of the fitness marketing strategies of today's fitness centers have shown the importance of different customer groups' levels of satisfaction regarding the centers' service quality. Most studies focused on customer satisfaction and service quality, but the four elements of the marketing mix and their role in the development of fitness centers' marketing strategies have been often overlooked (Chang, 2020;Andreasson and Johansson, 2021;Wang and Chiu, 2022). This study describes marketing strategies for the female market by examining the combination of the four elements of the marketing mix.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations